Sintomas do trato urinário inferior em homens idosos de um município do interior do Rio Grande do Sul - Winckler, Diego Carrão (2022)
Lower urinary tract symptoms (LUTS) predominantly affect elderly men after the sixth decade of life and have chronological age, metabolic syndrome and hormonal and anatomical changes as risk factors, such as loss of lean mass and prostatic hyperplasia. Our objective was to investigate the prevalence of LUTS and associated factors in elderly men in a city in the inland of Rio Grande do Sul. We conducted a cross-sectional study based on a population census of elderly people in the city of Coxilha-RS. Data were collected at home using a standardized and pre-coded questionnaire. Lower urinary tract symptoms were assessed using the International Prostate Symptons Score (IPSS) questionnaire. Erectile dysfunction was assessed using the International Index of Erectile Function-5 (IIFE-5) questionnaire. The other variables investigated were: age, marital status, means of housing, education, smoking, self-reported presence of diabetes mellitus (DM) and systemic arterial hypertension. Body mass and height measurements were also taken to calculate the Body Mass Index (BMI), waist circumference in centimeters (cm) and handgrip strength (HGS) using a manual dynamometer, with low values < 27Kgf; we performed descriptive statistics, measures of central tendency and dispersion, chi-square test and Poisson regression, calculation of the prevalence ratio and respective 95% confidence interval. A total of 253 men were interviewed; 243 (96.4%) responded to the IPSS and 231 (91.3%) responded to the IIFE-5; the overall prevalence of moderate/severe LUTS was 42.8%, with nocturia, intermittent voiding, frequency and weak voiding being the most common symptoms; most of the elderly were between 60 and 69 years old, lived with a partner, lived in rural areas, had between 4 and 11 years of schooling and were smokers or former smokers; adjusted analysis showed a higher prevalence of moderate/severe LUTS among elderly people with DM, overweight, low HGS and erectile dysfunction. The results of our study indicate a high prevalence of moderate and severe LUTS in the elderly male population; the association between LUTS and erectile dysfunction and diabetes indicates an important neurovascular component in the etiology of urinary symptoms; the association between HGS and LUTS indicates a relationship between muscle strength and urinary symptoms, and should be further evaluated in further studies.